The confluence of James Joyce and Guimarães Rosa - Silva, Francisco Ivan da (ABEI Journal, 2012)
This paper aims to show the similarities between two novels,Ulysses, by the Irish writer James Joyce, and Grande Sertão: Veredas, by the Brazilian author João Guimarães Rosa. A large number of comparisons have been made between these two novels in the field of literature. They have many things in common, mainly the use of language. It is creation; and, even more, it is poetry, a magic path leading one author to the other, a novel about the other novel; and yet more: the language is the magic magnifying glass that brings readers and authors closer to the solitary journey of the characters. It is in the poetry and expression of these narratives that the readers discover the “spirit” of creation.